The partially liberalized cocoa sector in Ghana: Producer price determination, quality control, and service provision - Kolavalli, Shashidhara; Vigneri, Marcella; Maamah, Haruna; Poku, John (International Food Policy Research Institute, 2012)
The cocoa sector in Ghana is one of few examples of an export commodity sector in an African country that has withstood the pressure to fully liberalize. Despite substantial government control over internal and external marketing via the Ghana Cocoa Board (COCOBOD), the current institutional arrangement is able to pass on a significant share of export prices to farmers, a key objective of the liberalization of commodity markets in Africa. As Ghana continues to capitalize on its recent discovery of off-shore oil reserves, the government and donors alike are concerned that the competitiveness of the cocoa sector may be threatened. The overall objective of this study is to examine the competitiveness of the cocoa sector by focusing on four aspects of the current set of institutions, including (1) the process of determining producer prices; (2) the outcomes of the introduction of private licensed buying companies; (3) COCOBOD’s role in maintain quality, and the costs and benefits of this process; and (4) trends in COCOBOD expenditure on the provision of various goods and services. The methodology adopted for this study is primarily that of an expenditure review.